Avicenna and Aquinas on the Negative Approach to the Attributes of God - hasan abasi hasan Abadi (حکمت اسرا, 2016)
Negative approach to speaking of divine attributes is an age-old discussion and has two main categories: the negation and silence and the negative-positive way. The negative-positive way has various interpretations and meanings. Some of them are in conflict with inexpressibility of the God, and others are not. Some of them are not in agreement with silence and have a positive approach about God. What is the meaning of negative-positive approach for Avicenna? What is the relation between this way and the inexpressibility of God for Avicenna? What is his purpose in using this way for expressing the divine attributes? In the present paper, after reviewing different meanings of negative-positive way for Avicenna and Aquinas, we will discuss Avicenna’s overall position (returning of all divine attributes to negation and relation) alongside the comparative analysis of Aquinas views.